Water-rock interaction and mixing processes of complex urban groundwater flow system subject to intensive exploitation: The case of Mexico City. (November 2020) - Olea-Olea, Selene; Escolero, Oscar; Mahlknecht, Jürgen; Ortega, Lucia; Taran, Yuri; Moran-Zenteno, Dante Jaime; Zamora-Martinez, Olivia; Tadeo-Leon, Javier
Abstract: In complex aquifer systems subject to intensive exploitation it is important to investigate hydrogeochemical processes in the components to understand the hydrodynamics of groundwater. In this respect, understanding the hydrochemical mechanisms of water-rock interactions and mixing processes eventually leads to the development of appropriate strategies for a sustainable groundwater management. In this study, we analyze water-rock interactions processes of the so-called Anáhuac groundwater system underlying part of the Mexico Valley comprising Mexico City and its suburbs. This intensively exploited system has four flow components: 1) local flow, 2) intermediate flow, 3) cold regional flow, and 4) hot regional flow. This is studied using inverse geochemical models, which consider uncertainties of analytical data and constraints from thermodynamic stability diagrams, speciation-solubility models, and petrographic data. Three representative modeling sections were selected for the implementation of the mass-balance approach. The general conceptual model in two sections suggests that rainwater infiltrates the subsoil and begins to dissolve CO2 in the unsaturated zone; by reaching the saturated zone it reacts with silicate minerals of the host rock producing the final chemical composition of waters. On the other hand, the third section shows mixing as the main groundwater process, as well as water-rock interactions. In general, the identified processes of water-rock interaction are dissolution of CO2, dissolution of calcite, gypsum, and halite, Ca/Na ion-exchange, and weathering of silicate minerals such as biotite, muscovite, plagioclase, epidote and pyroxene, and precipitation of kaolinite, SiO2 and Fe (OH)3 . Changes between local and intermediate flow components suggest dissolution of andesite rocks and precipitation of pyrite. Changes between local flow component and the cold regional component are explained by large flow trajectories. Transformations between local and hot regional components indicate mixing flows and a deep circulation influenced by the geothermal gradient. The combination of the methods used in this study can be applied in other similar geoenvironments of the world and assist local water authorities to adequately address and manage groundwater. Highlights: Geochemical models explain water-rock interaction in the flow components. Silicate weathering and mixing flows are main water-rock processes. Mixing quantification between thermal and non-thermal components was obtained. A systematic geochemical modeling approach was used in a complex flow system.